DISTRIBUTION OF ASSESSMENT VALUES OF PRE-SCHOOL CHILDREN WITH DIFFERENT DEVELOPMENTAL RATES - Cordier, Bálint; Kulcsár, György; H. Ekler, Judit (Stadium - Hungarian Journal of Sport Sciences, 2025)
In the past two decades, a strong negative trend can be observed in the development of the abilities of preschool children. Fewer and fewer children meet the criteria for school readiness by the age of six. Children with high levels of neurological immaturity do not even start school but are already lagging. The developmental deficit of partial skills is so significant that specific learning difficulties can be predicted as early as the end of kindergarten age. Although this large backlog can be made up, extra effort must be made on the part of both parents and teachers. With our research, we sought to answer whether the performance of preschool-age children, which deteriorates year by year, covers all partial abilities or if areas with a particularly negative trend can be identified. The most obvious tool for checking children’s neurological maturity is the measurement of motor and sensorimotor functions. Based on the measurement results of 58 large groups of kindergarten children (6 ± 1 years) with different developmental rates, we examined the values of the skills that need development and predicted the occurrence of learning difficulties in the examined sample. In the sensory and sensorimotor functions group (18 tests), 40 of the 58 children examined need to develop their gestalt vision. During the elementary movements (12 tests) examination, walking on the outer sole appeared to be an area for improvement in 39 out of 58 children. Among the examined areas of body perception (6 tests), the values of the sense of balance and the cross-schemes were the highest, with 31 points. The specialty of fine motor skills and hand use (3 tests) is that all test segments received a value above 30 points.